Computer Simulation of the Electric Transport Properties of the FeSe Monolayer - Sergeyev, D.; Zhanturina, N.; Myasnikova, L.; Popov, Anatoli I.; Duisenova, A.; Istlyaup, A. (Walter de Gruyter, 2020)
The paper deals with the model research of electric transport characteristics of stressed and non-stressed FeSe monolayers. Transmission spectra, current-voltage characteristic (CVC) and differential conductivity spectra of two-dimensional FeSe nanostructure have been calculated within the framework of the density functional theory and non-equilibrium Green's functions (DFT + NEGF). It has been shown that the electrophysical properties depend on the geometry of the sample, the substrate, and the lattice constant. On CVC of non-stressed sample in the range from -1.2 V to -1 and from 1.2 V to 1.4 V, a region of negative differential resistance (NDR) has been observed. NDR is at both signs of the applied voltage due to the symmetry of the nanostructure. d2I/dV2 is used to determine the nature of the electron-phonon interaction and the features of quasiparticle tunnelling in stressed and non-stressed samples. The results obtained can be useful for calculating new elements of 2D nanoelectronics. © 2020 D. Sergeyev et al., published by Sciendo 2020. --//-- Published under the CC BY 4.0 license.
The research has been supported by the grant of the Ministry of Education and Science of the Republic of Kazakhstan AP08052562. In addition, the research of AIP has been supported by the Latvian- Ukrainian Grant LV-UA/2018/2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; 2D-nanoelectronics; Current-voltage characteristics; FeSe monolayer; transmission spectra